Simulation of the Investment Attractiveness of Science in a Region - Tarasyev, Aleksandr Aleksandrovich; Krivenko, Ilya Arturovich; Pecherkina, Maria Sergeevna; Kashina, Tatiana Olegovna (Economy of Regions, 2016)
The article is devoted to the variable and disproportionate funding of science in the Russian economy. The paper is focused on the analysis of the Russian financial flows into scientific research and development. The paper explains the dynamics of the main investment flows trends into research and development, highlights the causes of financial flows variable dynamics directed to the high-tech industry. In the work, the investment situation in the Russian market was compared with the foreign experience. The genesis of the optimal financial distribution problems showed the need to develop a dynamic model with the built-in differential equations to forecast the behavioral dynamics of investment flows. We selected the statistical indicators, which have a significant impact on the dynamics of investment flows directed into science. To assess the dynamics of investment flows, we have developed a methodology, which provides a cumulative assessment of the territory investment attractiveness. The multifactor integral estimation allows to describe a data array, reflecting the accumulation of investment attractiveness over time depending on the dynamics of the resultant socio-economic proportional indexes. Due to the accumulation of a data array over time using a differential equation, it is possible to obtain a forecast of the volume of the territory investment attractiveness. The amount of the projected investment flows depends directly on the amount of the investment attractiveness accumulated for the previous step of model's time. The integrated assessment of the investment attractiveness of the scientific sector in the region allows to reveal the investors preference of the regions with a high concentration of research institutions and higher education institutes.